Services for Trade Competitiveness : Country and Regional Assessments of Services Trade - Hollweg, Claire H.; Sáez, Sebastián (Washington, DC: World Bank, 2019)
Recognizing that services affect the ability of countries and their firms to compete on international markets, the World Bank’s Trade and Regional Integration Unit has developed an extensive work program to promote the performance of countries’ domestic services sectors, including services trade. Services for Trade Competitiveness presents selected applications of new methodologies that were developed to assess the competitiveness of countries’ services sectors, discern the types of barriers to services that exist in the regulatory environment, and identify the resulting policy implications. Its assessments are designed for a wide audience, including policy makers in developing countries and development practitioners in international organizations, policy-making institutions, and academia. The purpose of this book is to help developing countries make informed policy choices to increase their chances of benefiting from the increasing prominence of services in international trade.